Adopted Children as Mahram: Responding to Ijtihad ‘Ā’isyah (614-679 Ad) in the Flow of Modernization - maizul imran; Beni Firdaus; Arsal Arsal (Jurnal Mahkamah : Kajian Ilmu Hukum Dan Hukum Islam, 2020)
Adoption of children in Islam can adjust to the habits (‘urf) of the community as long as it does not conflict with the principles of syara’. Likewise family life in Indonesian society still implements the habit of breastfeeding children (radhā ‘) to others. One of the Ijtihad ‘A’isyah believes that a child who is close to reaching baligh can become a maḥram with a mother who is breastfeeding him. This opinion must be understood by the principle of ihtiyāṭ (caution). Observing the authority of the Religious Court in determining the status of adopted children who adhere to the principle that between adopted children and adoptive parents is not a muhrim so they must maintain genitalia. Therefore ijtihad ‘A’isyah is an opportunity to be enforced by emphasizing the age limit of adopted children who are allowed to breastfeed, so that adopted children have the status of maḥram.